The Impacts of the COVID-19 Pandemic on the Consumer Behavior of Turkish Tourists - Jafari, Kaveh; Saydam, Mehmet Bahri; Erkanli, Emine; Olorunsola, Victor Oluwafemi (Univ Estado Rio Grande Norte, 2020)
Tourism sector has already affected severely by the existing coronavirus (COVID-19) epidemic as of Feb 11, 2020 started in China and spread all over the world. World Health Organization (WHO), therefore, has been recommended travelers to avoid travelling. Since then, the number of tourists has essentially plummeted to a level that world has not ever experienced before. In the view of the lacking studies in tourism literature that scrutinize by the subject. This study inspects the effect of the coronavirus (COVID-19) epidemic on the tourism industry by examining the effects of COVID-19 outbreak on the tourist behavior of Turkish travelers. Furthermore, this empirical study analyses into the sensitivity of tourists concerning crises in making decisions regarding travel. The analysis shows that COVID-19 outbreak has significantly affected people's life, work and travelling during the COVID-19 outbreak period while the impacts on individuals' inclination to travel, the preference of leisure trips and concern of public hygiene vary. In general, the influences of COVID-19 outbreak are of a nature of paroxysm and period, and the lessening of travel and tourism was triggered by a combination of internal motivation as well as external compulsory measures and travel bans. Additionally, the formation of an effective communication system and crisis action will add to the rescue of the tourist market.
Keywords: COVID-19; consumer behavior of tourists; pandemic; Turkey